Classic Russian Poetry in Spanish: An Essay on the Experience and Problems of Translation - M. A. Cornejo Ubillús (Ибероамериканские тетради)
It is thanks to translation, which is a challenging yet indispensable task, that Russian literature has come to be well known among the peoples of Latin America and has had a positive influence on their culture and spiritual development. Readers have been able to enjoy and appreciate many prose works by great Russian writers in Spanish. On the contrary, Russian poetry, which has also appealed to the Latin American audience, has not become as popular as the prose. Readers have had access to works by few Russian poets, with some of these poems translated from French or English. It is only recently that more poems have been translated directly from Russian into Spanish, which has attracted the interest of the public and has helped to promote classic works by distinguished Russian authors, such as A. Pushkin, M. Lermontov, S. Esenin, A. Blok, A. Akhmatova and M. Tsvetaeva. These recent advances in poetry translation raise certain issues, for instance, the technical difficulties of translating poetry in general and poems in Russian in particular, as well as the knowledge and skills it takes a translator to tackle poetry. In addition, a growing interest in Russian poetry translation begs the question of whether quality translation of poetry, especially that by eminent authors, is possible at all. Translation of poetry from Russian into Spanish allows readers to get to know the Russian world, understand its culture, humanistic and spiritual values, and, therefore, serves as a tool of intercultural communication and helps to strengthen cultural ties between Russia and Latin America.